CANINE SERVICE OF CUSTOMS AUTHORITIES AND ITS ROLE IN DETECTING SMUGGLING (World Bulletin of Management and Law, 2024)
The article analyzes the role of the cynological service of the Republic of Uzbekistan in detecting smuggling and other offenses in the customs sphere, as well as the main directions for improving the activities of the National Cynological Center and the effectiveness of the use of cynologists to protect the economic security of our country
Keywords: Smuggling; offenses; narcotic drugs